Indicadores de inserção de intervenções de qualificação urbana em cidades de médio porte: o caso de Santa Maria - Correa, Amanda Silveira (2022)
This work sought to understand the dynamics existing in cities and their consequences. These consequences generate urban problems such as segregation, social inequalities and criminality. In an attempt to understand how urban qualification interventions can bring more vitality to these areas, helping to minimize such problems, this work aims to develop a methodological procedure to identify ideal places for the insertion of microscale interventions aimed at urban qualification in medium-sized cities. . The methodological procedures developed and applied are divided into three stages and help to analyze the neighborhoods of the city of Santa Maria, Rio Grande do Sul under four chosen indicators. The indicators chosen for the analyzes and mapping carried out were data on economic vulnerability, crime, data referring to urban voids existing in the city's fabric and data on community belonging and organization (obtained through interviews with managers and municipal employees). These indicators present needs and potentials of the neighborhoods of the analyzed city, in this sense, at the end of the work it was possible to arrive at the result of the most indicated neighborhoods to receive urban qualification interventions in the city of Santa Maria.